Attitudes to IT-Security When Using a Smartphone - Benenson, Zinaida; Hintz, Nadina; Kroll-Peters, Olaf; Krupp, Matthias (SOUPS, 2012)
While mobile devices are becoming more and more powerful, the number of potential security threats is increasing. Although the important role of users in the realization of IT security measures is widely acknowledged and documented, research in the area of mobile security mostly concentrates on technical means. In this work we take the first step in examining the role of the users in the IT security of mobile devices. We present mental models of security that are based on the results of interviews with 24 users. Mental models are the representation of reality in people's mind and can be inaccurate or faulty. Mental models are very helpful for behavior prediction. Thus, mental models of security form the basis of users' efforts to protect their devices. © 2012 Polish Info Processing Socit.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.lehrst.attitu

Faktoren des datenschutzbewussten Verhaltens in Facebook - Hintz, Nadina; Benenson, Zinaida (DACH Security 2013, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.lehrst.faktor_3

Friendship in German Online Social Networks - Hintz, Nadina; Benenson, Zinaida; Strufe, Thorsten (SOUPS, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.lehrst.friend_5

Susceptibility to URL-based Internet Attacks: Facebook vs. Email - Benenson, Zinaida; Hintz, Nadina; Girard, Anna; Luder, Andreas (6th IEEE International Workshop on SEcurity and SOCial Networking, 2014)
The usage of social networking sites has been steadily increasing in the last decade. Communication via social networks has replaced email as the traditional means of electronic communication in many contexts. Accordingly, many types of Internet fraud also spread to social networks. In this work, we make the first to our knowledge direct comparison of users' susceptibility to attacks that involve clicking on dangerous links in Facebook messages versus in emails. We conducted a between-subjects quasi-experiment with 398 users where the users received links from strangers in a Facebook message or via email. We observed the respective clicking behavior and investigated users' attitudes to URL-based attacks by means of a post-experimental survey. Our results show that the communication medium (Facebook vs. email) leads to significant differences in attack susceptibility. Quite surprisingly, the success rate of email-based attacks is significantly higher. © 2014 IEEE.
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.lehrst.suscep